Dynamic public transit accessibility using travel time cubes: Comparing the effects of infrastructure (dis)investments over time. (March 2017) - Farber, Steven; Fu, Liwei
Abstract: We put forward a new data object called the public transit travel time cube and demonstrate how the cube can be used in the analysis of transit travel time changes over space and time. The travel time cube contains the shortest path transit travel time between sets of origins and destinations in the city, at all times of day. Once computed, a wide range of investigations become readily available to the transit planner or transportation researcher. We conduct three demonstrative analyses using travel time cubes for the Wasatch Front, Utah and the Portland region in Oregon. Our studies investigate how travel times were impacted by service cuts and expansions in the two regions respectively and the impact this had on jobs accessibility. We also use the travel time cube to study the last mile problem, and compute the travel time savings and the stability gained by solving the last mile problem with bicycling. The paper concludes with an expanded discussion on the merits of the travel time cube and outlines four avenues for continued research. Highlights: We introduce the public transit travel time cube containing the shortest path transit travel times between sets of origins and destinations in the city, at all times of day. The transit travel time cube is used to compare how transit travel times and accessibility have changed in response to network and service modifications. The travel time cube is used to quantify the impact of cycling on travel time stability.